Faktor Determinan Pemicu Korupsi di Sektor Pemerintahan (Studi pada Pegawai Negeri Sipil di Jakarta) - Harti Budi Yanti (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2020)
Mutual funds performance is one of the most important method to measure the capability of Mutual funds, this method will answer your question whether the mutual funds can be used as a good priority in investment or not. Beside that, the manager’s ability in selecting share also play the big role, since the choice that made by the manager will determine how much “return” will be received by the investors. After that, the high risk in investment, which later will show up, should be considered before taking the final decision in selecting share.This study aimed to verify the effect of share selection and the level of risk on the performance of mutual fund sharesThe data used in this study is the share of mutual funds in 2009-2011 and the samples are 18 mutual funds selected by using purposive sampling method. The data are obtained from the NAB of each fund which can be obtained at Bapepam-LK. Based on the results of hypothesis for regression models, we found out that selecting share give a great influence on Mutual funds performance and the level of risk has no significant effect on the in Mutual funds performance.